Effect of high protein supplementation on growth and nutrient digestibility of broiler (Bangladesh Journal of Animal Science, 2017)
This study was undertaken to compare the growth performance and nutrient digestibility (energy, protein and amino acid) of broilers fed diets containing only vegetable protein (soybean) with birds that received Pro-EL as protein supplement in their diets. Day-old male broiler chicks (n=60; Cobb 500) were randomly distributed into 2 dietary treatment groups, namely control (T1) and supplemented (T2) diets, with 5 birds per replication in a CRD. Birds had a free access to iso-caloric and iso-nitrogenous starter diets in cages up to 21d.  The results of FI, LW, LWG and FCR of broilers up to 21 days were poorer (P0.05), but the majority of the AAs digestibility values were influenced (P